Pengaruh Harga Dan Kualitas Produk Terhadap Keputusan Pembelian Buah Lokal Di Pasar Tradisional Caringin Kota Bandung - Septiani, Suci; Somadi (CV. SINAR HOWUHOWU, 2025)
Regular consumption of fruits plays an essential role in maintaining the immune system due to their rich content of vitamins and minerals. In Indonesia, as a tropical country with abundant biodiversity, the dynamics of fruit consumption and production show an interesting development. This study aims to identify and analyze the influence of price and product quality on the purchase decisions of local fruits at the Caringin Traditional Market in Bandung City. The research employed a quantitative approach with a total sample of ninety-six respondents. Data were collected through questionnaires and supported by literature studies. The findings indicate that, partially, price does not have a significant effect on purchase decisions, whereas product quality has a strong influence on consumer preferences. Overall, both price and product quality jointly have a significant impact on the decision to purchase local fruits. These findings suggest that although price is not the main determinant in purchase decisions, product quality plays a dominant role in shaping consumer choices. Therefore, traders in traditional markets are encouraged to prioritize improving the quality of local fruits to maintain and enhance competitiveness against imported products.